LINGÜÍSTICA INGLESA APLICADA: ORIGEN, EVOLUCIÓN Y FUTURO - Abello Contesse, Christián (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper looks at the development of applied English linguistics as an academic domain during the second half of the twentieth century. By focusing on some frequent problems related to the definition and interpretation of contemporary applied linguistics, the paper gives an account of its origins, its recent growth, and its present scope. On the basis of this objective description, a tentative—and somewhat speculative— account of applied linguistics is provided which focuses on some selected developments and trends that are likely to take place within this field as it meets the challenges of the twenty-first century